775 The Effect of Anti-Seizure Medication Administration on Mortality and Early Post Traumatic Seizures In Critically Ill Older Adults With Traumatic Brain Injury. (April 2023) - Glaser, Adam; Kanter, John; Martinez-Camblor, Pablo; Buhl, Lauren; Anderson, Matthew; Pannu, Ameeka; Shaefi, Shahzad; Taenzer, Andreas; Boone, Myles Dustin
Abstract : INTRODUCTION: Older adults (≥65-years) are an understudied and growing TBI population. Guidelines support prophylactic antiseizure medication (ASM) to reduce early posttraumatic seizures (ePTS) (within 7-days of injury) in severe TBI. Whether ASM decreases mortality or ePTS in this population remains unclear. This study assesses association between ASM administration, mortality, and seizure in older TBI patients. METHODS: This retrospective cohort study utilized data from the Massachusetts Institute of Technology, Medical Information Mart for Intensive Care-III (MIMIC). Our cohort included patients 65-years or older. Primary exposure was early ASM administration in TBI patients admitted to an ICU at a Level 1 trauma center from 2001-2012. A double-robust inverse propensity scale weighted model based on proportional hazard and logistic regression models assessed the association between ASM administration and risk of death within 7-days of admission. RESULTS: Of 1, 145 patients, 783 (68.4%) received ASM within the first 24 hours. TBI severity, classified by Glasgow Coma Score (GCS), was predominantly mild (71.2%) followed by moderate (16.8%), and severe (11.3%). Patients who received ASM were less likely to have died at 7-days (adjusted Death HR = 0.48 [95% CI 0.28–0.88] P = 0.005), at 30 days (adjusted HR 0.67 [0.45–0.99] P = 0.045) and at one year (adjusted HR 0.72 [0.54–0.97] P = 0.029). There was no difference in seizure (adjusted Seizure OR 1.18 [0.61–2.26] compared with those who did not receive ASM. CONCLUSIONS: Early ASM administration was associated with reduced mortality at 7-days, 30-days, and one-year, but did not affect early seizure risk. This observed benefit in older adults with all TBI severity suggest broader recommendations for ASM use.